MANAGING CONSUMER BEHAVIOR: THE ROLE OF ANIMOSITY, ATTITUDES, AND SOCIAL NORMS FROM A BUSINESS PERSPECTIVE IN INDONESIA - Saifudin, Saifudin; Arinta, Yusvita Nena; Waluyo, Agus; Bahjatullah, Qi Mangku; Musthofa, Nur Huri; S, Anisa Dewi; Krisyanti, Reva Dwi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the factors influencing the desire of non-Muslims in Indonesia to boycott Israeli-affiliated products. Using a quantitative approach with survey data collection techniques, the study involved 1,791 respondents spread across 34 provinces in Indonesia. So that the results of this research have a high level of representativeness. The research model tested the influence of three independent variables, namely animosity, attitude, and subjective norm, on the dependent variable, namely willingness to boycott. Data were analyzed using the Structural Equation Modeling (SEM) method with Smart PLS 3.2.9 software. The results showed that all three independent variables had a positive and significant effect on the desire to boycott. This fact can be used to strengthen that the findings of this study are not merely a local phenomenon, but reflect a broader pattern in non-Muslim society in Indonesia. These findings provide important insights for developing marketing strategies and managing international relations in the Indonesian context. The implications of this research also suggest that companies and stakeholders should consider psychological and social factors when designing marketing campaigns, particularly those related to products affiliated with specific countries.